Deeping the roots of children’s participation - Cath, Larkins (Sociedad e Infancias, 2023)
In the field of childhood studies and child rights activism there is a strong commitment to supporting children's participation in public decision making. There are growing examples of this in practice across Europe. But it is rarely inclusive of marginalised children and can tend to focus on voice rather than action. This article, developed from a recent conference presentation, reflects on15 years of the author's practice and academic work. It suggests that fertile ground for deeper and strongly rooted examples of impactful and inclusive children's participation by picking apart existing participatory processes using a lense of citizenship, challenges, agency and time. This might enable us to dare to consistently name the risk that child participation can become an exercise in neoliberal citizenship, to steer practice towards more radical notions of participation as direct influence over resources (rather than voice) and to help ground calls for action in an understanding of the longterm patterns of inequality that many children are confronting.